2014
DOI: 10.1155/2014/835914
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory and Antihyperalgesic Activities of Ethanolic Extract and Fruticulin A from Salvia lachnostachys Leaves in Mice

Abstract: The anti-inflammatory and analgesic effects of the ethanolic extract (SLEE) and fruticulin A from the leaves of Salvia lachnostachys were evaluated in mice, using experimental models of inflammation (paw oedema and pleurisy induced by carrageenan injection) and hyperalgesia (electronic Von Frey). Oral administration of SLEE (30, 100, and 300 mg/kg) and fruticulin A (0.3 and 3.0 mg/kg) decreased the total leucocytes number in pleural lavage, protein extravasation, and paw oedema. SLEE (100 mg/kg) and fruticulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…Carrageenan-induced paw edema is a commonly used model for acute inflammation study [ 20 , 21 ]. The acute inflammatory response induced by carrageenan injection involves two phases [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carrageenan-induced paw edema is a commonly used model for acute inflammation study [ 20 , 21 ]. The acute inflammatory response induced by carrageenan injection involves two phases [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated a potent antimicrobial activity of essential oils against various microorganisms [3,4]. The antimicrobial potential of these oils has been attributed to the secondary metabolites [5,6]. Vitex agnus-castus L. (VAC) (Verbenaceae) is a deciduous shrub that is native to Mediterranean region, Europe, and Central Asia [7].…”
Section: Introductionmentioning
confidence: 99%
“…for the ketamine group (1 mg/kg, positive control). The dose of SLEE was determined based on a previous study by our group [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…elegans have been reported [ 2 5 ]. Studies have demonstrated anti-inflammatory and antinociceptive effects in different Salvia species [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation